Long-term stability and condylar remodeling after mandibular advancement: A 5-year follow-up - Ehardt, Lauren; Ruellas, Antonio; Edwards, Sean; Benavides, Erika; Ames, Matthew; Cevidanes, Lucia (American journal of orthodontics and dentofacial orthopedics, 2021)
This study evaluated whether presurgical characteristics, the magnitude of mandibular advancement, and changes in mandibular plane angle are correlated with long-term stability and postsurgical condylar remodeling and adaptations using 3-dimensional imaging. Forty-two patients underwent bilateral sagittal split osteotomies for mandibular advancement using rigid fixation. Cone-beam computed tomography (CBCT) scans were acquired before surgery (T1), immediately after surgery (T2), and at long-term follow-up (T3). The average follow-up period was 5.3 ± 1.7 years after surgery. Anatomic landmark identification on the cone-beam computed tomographies and subsequent quantification of the changes from T1 to T2 and T2 to T3 were performed in ITK-SNAP (version 2.4; itksnap.org) and 3DSlicer (version 4.7; http://www.slicer.org) software. Surgical displacements, mandibular plane angle changes, and skeletal stability were measured relative to cranial base superimposition, whereas condylar remodeling was measured relative to regional condylar registration. Partial correlation coefficients were used to assess relationships between clinical and surgical variables, condylar remodeling, and long-term surgical relapse while controlling for variability in the length of follow-up. B-point relapsed more than 2 mm posteriorly in 55% of the patients. The only variables strongly associated with the posterior movement of B-point long-term were mesial yaw of the condyle during surgery (P ≤0.01) and the length of follow-up from T2 to T3 (P ≤ 0.01). There was no relationship between the magnitude of advancement or presurgical mandibular plane angle and relapse or condylar resorption. Condylar resorption was strongly associated with relapse of B-point in the posterior direction (P ≤0.01) and clockwise rotation of the mandibular plane long-term (P ≤0.01). Twenty-nine percent of subjects showed resorption of more than 2 mm in the inferior direction at the lateral pole, and 17% of the subjects showed resorption of more than 2 mm in the inferior direction at condylion. Compared with male subjects, females exhibited significantly greater condylar remodeling (P ≤0.01) and slightly greater relapse at B-point (P ≤0.05). Surgical relapse at B-point may occur slowly over time and is primarily due to condylar resorption in mandibular advancement patients. Mesial yaw of the condyle during surgery may lead to condylar resorption postsurgically. In addition, females are at greater risk of condylar resorption postsurgically. •The length of the follow-up period was associated with the posterior movement of B-point.•Relapse may occur over time.•Mesial yaw of condyle during surgery was associated with relapse of B-point.•Condylar resorption was associated with relapse of B-point long-term.•Females exhibited greater condylar remodeling and slightly greater relapse at B-point.